THE STUDY OF THE ECOLOGY OF THE ALGAE OF SEWAGE AS BIOTECHNOLOGICAL DISCIPLINES (Web of Teachers: Inderscience Research, 2025)
This article presents the natural composition and seasonal changes in algae treatment facilities of Bukhara region.